Pengaruh Corporate Social Responsibility terhadap Corporate Image dan Perilaku Word of Mouth - Sura Ningrum, Lily; Nurcahya, I Ketut (E-Jurnal Manajemen, 2014)
Business paradigm is changing. CEO was only oriented to the shareholder. Today, CEO must be oriented to the stakeholders too. Business people are having a good deal by doing the social responsibility or known as Corporate Social Responsibility (CSR). CSR is the effort that corporate did to decrease the negative impact and increase positive impact from their activity. The purpose is analyzing the influence of CSR to corporate image and WOM behavior and also to analyze the mediation of corporate image through CSR and WOM behavior. Using the structural equation modeling method, the result shows that CSR influenced to corporate image and WOM behavior whereas corporate image has the role of mediation. Keywords: corporate social responsibility, corporate image, WOM
Keywords: corporate social responsibility; corporate image; WOM